Comparative effects of motor and cognitive dual task gait training on Balance, Spasticity and quality of life in patients with Diplegic Cerebral Palsy - Sana Kamran,; Mehwish Saghir,; Sania Maqbool,; Anza Amjad,; Joail Thomas,; Meerab, (Al-Qanṭara, 2023)
Cerebral palsy (CP) is a neurodevelopmental disorder affecting motor skills and muscle tone, often associated with concurrent cognitive impairments. A growing body of evidence supports implementing dual-task gait training for enhancing functional mobility and cognitive performance. However, its impact on children with diplegic cerebral palsy remains under-researched. Objective: This study aimed to compare the effects of motor and cognitive dual-task gait training versus conventional therapy on balance, spasticity, and quality of life in children with diplegic cerebral palsy. Methods: A total of 52 participants, aged 6-12 years with diplegic CP, were randomized into two groups. Group 1 received conventional therapy (n=26), and Group 2 received motor and cognitive dual-task gait training (n=26). The interventions were conducted over eight weeks. Assessments, including the Gait Profile Score (GPS), Pediatric Berg Balance Scale (PBS), Gross Motor Function Classification System (GMFCS), and Cerebral Palsy Quality of Life (CP-QOL) were conducted at baseline, Week 4, and Week 8. Results: The Dual-Task Gait Training Group demonstrated significant improvements in the GPS, PBS, GMFCS, and CP-QOL scores at Week 8 compared to the Conventional Therapy Group. Expressly, significant differences were noted in balance (PBS: p<0.001), spasticity (GPS: p<0.001), gross motor function (GMFCS: p<0.001), and quality of life (CP-QOL: p<0.001). Conclusion: The findings suggest that motor and cognitive dual-task gait training could be more effective than conventional therapy for improving balance, reducing spasticity, and enhancing the quality of life in children with diplegic cerebral palsy. Keywords: Diplegic Cerebral Palsy; Dual-Task Gait Training; Conventional Therapy; Quality of Life; Balance